2020
DOI: 10.1371/journal.pone.0241251
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with poor clinical outcomes of ST-elevation myocardial infarction in patients with door-to-balloon time <90 minutes

Abstract: Background Recent guidelines for ST-elevation myocardial infarction (STEMI) recommended the doorto-balloon time (DTBT) <90 minutes. However, some patients could have poor clinical outcomes in spite of DTBT <90 minutes, which suggest the importance of therapeutic targets except DTBT. The purpose of this study was to find factors associated with poor clinical outcomes in STEMI patients with DTBT <90 minutes. Methods This retrospective study included 383 STEMI patients with DTBT <90 minutes. The primary endpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…24) The initial thrombolysis in myocardial infarction (TIMI) flow grade, final TIMI flow grade, and TIMI thrombus grade were recorded from coronary angiography. 11,25) Statistical analysis: Data are expressed as the mean ± SD or percentage. Categorical variables are presented as numbers (percentage) and were compared using Fisher's exact test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…24) The initial thrombolysis in myocardial infarction (TIMI) flow grade, final TIMI flow grade, and TIMI thrombus grade were recorded from coronary angiography. 11,25) Statistical analysis: Data are expressed as the mean ± SD or percentage. Categorical variables are presented as numbers (percentage) and were compared using Fisher's exact test.…”
Section: Methodsmentioning
confidence: 99%
“…10) It is also known that Killip class !2 is associated with favorable clinical outcomes in patients with AMI. 11,12) However, the clinical outcomes in patients with Killip class 3 were not consistent among different reports, [13][14][15] suggesting that the severity of Killip class 3 varies widely from simple pulmonary edema to pulmonary edema complicated with a pre-shock state. Moreover, the clinical factors associated with poor clinical outcomes have not been sufficiently investigated in AMI patients with Killip class 3.…”
mentioning
confidence: 94%
“…One of the factors that decreased mortality of STEMI patients is early PCI that suggested that door to balloon time <90 min. [ 38 39 40 ] Our study considered time interval between arrival at PCI hospital and reperfusion therapy. We found longer mean of this time in our patients who died.…”
Section: Discussionmentioning
confidence: 99%
“…We also calculated the estimated glomerular filtration rate (eGFR) using serum creatinine (Cr), age, weight, and gender according to the following formula: eGFR 194 Cr 1.094 age 0.287 (male), or eGFR 194 Cr 1.094 age 0.287 0.739 (female) 21) . The initial thrombolysis in myocardial infarction (TIMI) flow grade and final TIMI flow grade were recorded from coronary angiography 22) .…”
Section: Introductionmentioning
confidence: 99%